Notable range extension of the genus Biramus Oswald, 1993 (Neuroptera: Hemerobiidae) and first record in Colombia - Camilo Castillo-Avila; Dennis Castillo-Figueroa (Universitas Scientiarum)
Biramus Oswald, 1993 is a hemerobiid genus (Neuroptera) distinguished by forewing morphological traits. This genus is distributed in Venezuela, Panama, Costa Rica, and Mexico. Here, we report Biramus in Colombia for the first time, based on a single female specimen collected in an upper Andean tropical mountain forest at an altitude above 3 000 m, in Guasca - Cundinamarca. This new record extends the genus’ distribution by 440 km in the northwestern region of South America and represents its highest altitudinal record, expanding its elevational distribution by 1373 m.